Factors associated with fragility in older adults hospitalized in surgical services. - Leguía-Cerna , Juan Alberto (2022)
Objective: To identify the factors associated with frailty in older adults hospitalized in surgical services of a Lambayeque hospital, March-June 2019. Materials and Methods: Analytical cross-sectional observational quantitative study. The elderly patients of the surgical services of the Almanzor Aguinaga Asenjo National Hospital were evaluated during 2019. A collection sheet and validated scales were used to comprehensively assess the elderly; The sample consisted of 358 patients; the sampling was census type. Results: The mean age was 75 years (± 9 years). The most frequent gender was male 184 people (51.4%). Cardiological risk III was associated with frailty in the bivariate analysis, of the 46 complication cases, 30 were frail patients (2 out of 3). 105 frail patients (29%) and 137 pre-frail patients (38%) were found. Conclusion: The factors associated with frailty were: female gender, illiterate or primary level, low and high comorbidity, patients with probable dementia, with social risk, with malnutrition and with abnormal hemoglobin; the mean age was 75 years (± 9 years), with a mean intake of 3 drugs per day (± 2 drugs) and the most frequent comorbidity was arterial hypertension, followed by type 2 Diabetes Mellitus without target organ injury, and less frequent were peripheral arterial disease followed by mild liver disease.